The 1.5°C climate and energy scenarios: impacts on economic growth. (17th March 2022) - Ekins, Paul; Drummond, Paul; Scamman, Daniel; Paroussos, Leonidas; Keppo, Ilkka
Abstract: In the context of calls for 'de-growth' (reduction in gross domestic product, [GDP]) in developed countries for them to be able to reduce emissions to 'net zero' in time for the temperature target in the Paris Agreement to be met, this article explores the various impacts on economic growth in the scenarios of the Intergovernmental Panel on Climate Change (IPCC) that limit the average global temperature increase in 2100 to 1.5°C. It finds that the impacts are generally small and that in no case is 'degrowth' required, although the requirements for the rate and nature of technological developments are challenging. The article then reports on a modelling exercise that investigates in more detail the economic dynamics of achieving the 1.5°C target. It finds that, as with the IPCC scenarios, and assuming the feasibility of at-scale deployment of carbon capture and negative emission technologies, economic growth continues throughout this century, with a major contribution coming from the investment required to decarbonise the energy system. Abstract : In the context of calls for 'de-growth' (reduction in GDP) in developed countries for them to be able to reduce emissions to 'net zero' in time for the temperature target in the Paris Agreement to be met, this article explores the various impacts on economic growth in the IPCC scenarios that limit the average global temperature increase in 2100 to 1.5°C. It finds that the impacts are generally small and that in no case is 'degrowth' required, although the requirements for the rate and nature of technological developments are challenging. The article then reports on a modelling exercise that investigates in more detail the economic dynamics of achieving the 1.5°C target. It finds that, as with the IPCC scenarios, and assuming the feasibility of at-scale deployment of carbon capture and negative emission technologies, economic growth continues throughout this century, with a major contribution coming from the investment required to decarbonise the energy system. Graphical Abstract: